Answers

2015-07-12T16:15:45+05:30
Zero of 3x+1 = -1/3
substituting -1/3 by x
we get 
(-1/3)³+3×(-1/3)²+3×-1/3+1
-1/27+1/3-1+1
=-1/27+1/3
=8/27
1 5 1
The Brainliest Answer!
2015-07-12T16:19:36+05:30
To find the remainder,

1. first equate the divisor( or 3x+1) to 0 and find the value of x.
so 3x + 1 = 0
⇒ 3x = -1
⇒ x = -1/3

2. Now find the value of the dividend( or x³ + 3x² +3x +1) at that value of x.
putting x = -1/3
x³ + 3x² +3x +1
= (-1/3)³ + 3×(-1/3)² + 3×(-1/3) + 1
= -1/27 + 3×(1/9) + 3×(-1/3) + 1
= -1/27 + 1/3 - 1 + 1
= 1/3 - 1/27
= (9-1) / 27
= 8/27

Remainder is 8/27.
2 5 2
i also got the same
:)
guys thnks a lot
you are welcome!
my pleasure